Titik Lelah Peradaban dalam Dinamika Oligarki: Tinjauan Sosiologis dan Eskatologis (Studi Geopolitik Perang Amerika Serikat-Israel vs Iran) - Qomarullah, Muhammad; Muklis; Febriansyah, Irlan (STAI Bumi Silampari, 2026)
This research report presents an in-depth analysis of the phenomenon of civilization's tipping point triggered by the increase in unsustainable socio-political complexity, the dominance of oligarchic businesses in modern democratic structures, and the normalization of wealth accumulation without a productive process (rent-seeking). This study aims to analyze the phenomenon of